Mathematics anxiety in mathematics problem solving among primary schools students - Kashefi, Hamidreza (2022)
This paper present results of a study that investigate students with different level of mathematics anxiety in solving mathematics problems. The sample of the study involved 120 students from four primary schools in Kulaijaya district, Johor, Malaysia. Data collected through survey-based questionnaires. The instruments adapted include Mathematics Anxiety Scale, A Study on Level of Problem Solving Skills and Choices of Problems. Findings indicate that there is a significant relationship between mathematics anxiety and problem-solving skills among the students. It was found that the reasons for choosing a problem to solve first by students with high mathematics anxiety include easy problem, understand the problem, minimum time required, maximum time required, minimum working required, difficulty of the problem, liking, order of the problem, confidence, interesting, short question, and lower order thinking required. The high mathematics anxiety students assert the choice made in choosing the problems was based on their mathematics problem solving skills. Further reflection on their emotions or feelings on choosing which problem to solve first relate to confident, feeling successful and satisfied. While choosing the last question to solve is associated with the feeling of stress, anger, and frustration. The findings highlighted a concern in addressing mathematics anxiety among primary school students, considering these students are still at the early stage of formal education.